2016
DOI: 10.3171/2015.6.jns15639
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of increased brain amyloid in severe TBI survivors at 1, 12, and 24 months after injury: report of 2 cases

Abstract: Traumatic brain injury (TBI) is a major risk factor for Alzheimer’s disease. With respect to amyloid deposition, there are no published serial data regarding the deposition rate of amyloid throughout the brain after TBI. The authors conducted serial 18F-AV-45 (florbetapir F18) positron emission tomography (PET) imaging in 2 patients with severe TBI at 1, 12, and 24 months after injury. A total of 12 brain regions were surveyed for changes in amyloid levels. Case 1 involved a 50-year-old man who experienced a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…PET) to identify neuropathological processes that might be activated following TBI, and could hence provide signatures for the cognate neurodegenerative diseases. Key processes that have started to be characterised in this context include amyloid deposition, [101][102][103][104][105] tau deposition, 104,106 and neuroinflammation. [107][108][109] Although the location and progress of pathology on MRI can provide useful clues to underlying neuropathology, the data from molecular imaging techniques provide insights that cannot be achieved even with advanced MRI.…”
Section: Late Neuropathology Of Tbimentioning
confidence: 99%
“…PET) to identify neuropathological processes that might be activated following TBI, and could hence provide signatures for the cognate neurodegenerative diseases. Key processes that have started to be characterised in this context include amyloid deposition, [101][102][103][104][105] tau deposition, 104,106 and neuroinflammation. [107][108][109] Although the location and progress of pathology on MRI can provide useful clues to underlying neuropathology, the data from molecular imaging techniques provide insights that cannot be achieved even with advanced MRI.…”
Section: Late Neuropathology Of Tbimentioning
confidence: 99%
“…The uptake of amyloid tracer 11 C-Pittsburgh compound B 11 C-PiB increases in all cortical gray matter and striatum in acute and chronic stages and in the posterior cingulate cortex in the chronic stage. 8,9 Other studies using 18 F-florbetapir have shown increased uptake in the frontal, temporal, and parietal cortices, striatum, and hippocampus in the chronic stage following TBI 10,11 . Sites of amyloid pathology are diverse in TBI populations because brain damage is usually spatially heterogeneous, depending on the injury type and its severity and the location of the impact.…”
Section: Introductionmentioning
confidence: 99%
“…Gatson et al . conducted serial amyloid PET imaging in two patients with severe TBI at 1, 12, and 24 months after injury and reported that within 2 years after severe TBI, amyloid had accumulated at both early and late time points . In contrast, Kawai et al .…”
Section: Discussionmentioning
confidence: 99%
“…1 Gatson et al conducted serial amyloid PET imaging in two patients with severe TBI at 1, 12, and 24 months after injury and reported that within 2 years after severe TBI, amyloid had accumulated at both early and late time points. 2 In contrast, Kawai et al examined 12 patients with posttraumatic neuropsychological impairment from the chronic stage to 10 years after TBI and reported that 11 C-labelled PiB was positive in three patients and negative in the other nine. 3 We ascribe the disagreements among these previous reports to the heterogeneity of the TBI-related neurodegenerative pathology.…”
Section: Discussionmentioning
confidence: 99%